2021
DOI: 10.4038/jas.v16i2.9323
|View full text |Cite
|
Sign up to set email alerts
|

Organic Matter Decomposition and Nutrient Release from Different Dhaincha (Sesbania spp.) Genotypes

Abstract: to July 2018 to compare the biomass yield potential, decomposition and nutrients release pattern of different dhaincha genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The higher biomass producing genotypes at later stages (40 to 60 DAS) will be more useful for green manure production and add more nutrients to the follow-up crops. Long-term green manure crop cultivation can improve the fertility of the soil, the productivity of the crops, and soil organic matter Chanda et al (2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher biomass producing genotypes at later stages (40 to 60 DAS) will be more useful for green manure production and add more nutrients to the follow-up crops. Long-term green manure crop cultivation can improve the fertility of the soil, the productivity of the crops, and soil organic matter Chanda et al (2021).…”
Section: Resultsmentioning
confidence: 99%
“…It can grow in a wide range of soil conditions and it is one of the best sources of organic matter which improves the fertility of the nutrient deficit soil. Soil Organic Matter (SOM) enhances the aeration of the soil, and moisture retention capacity by releasing nutrients (Chanda et al, 2021). SOM has declined to 0.3 -0.4 per cent in the cultivable lands of India.…”
Section: Introductionmentioning
confidence: 99%
“…As stated by Chanda et al [33], organic matter that is wholly decomposed has the available nutrients more quickly absorbed by plant roots. Leaf area is the main parameter because the rate of photosynthetic growth per unit plant is dominantly determined by leaf area [44].…”
Section: Leaf Areamentioning
confidence: 92%
“…As reported by Abayomi and Adebayo [32], compost can increase the height of spinach plants because compost contains mineral components that are beneficial for spinach. According to Chanda et al [33], wholly decomposed organic matter has its available nutrients more quickly absorbed by plant roots. Previous research by Chaudary et al [34] showed that the use of biological fertilizers can increase plant height.…”
Section: Plant Heightmentioning
confidence: 99%
“…Further, decomposed materials of Sesbania also serve as chelating compounds and help in increasing the availability of metallic micronutrients like Zn, Cu, Mn in succeeding crop [37]. Incorporation of dhaincha remarkably increased soil pH, organic carbon, N, P, K and S compared to initial soil nutrients status at the peak period of 50 days after incorporation and declined thereafter except in soil pH, K and S [94].…”
Section: Fig 5 Soil Enrichment With N By Fixation and Mineralization ...mentioning
confidence: 99%